2007
DOI: 10.1590/s1517-83822007000200005
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobia amylase production using various starchy substances as carbon substrates

Abstract: Six isolates of indigenous rhizobia of Central Amazonia were screened for the production of amylases in liquid media using various starchy substances as carbon sources. All rhizobia strains could produce more extracellular protein, biomass and amylases with the different kinds of carbon substrates. Among the carbon sources tested maltose was the best substrate for protein and amylase production. In general, peach palm flour and corn starch (maizena ® ) were also considered to be good carbon sources for rhizobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 37 publications
2
21
0
1
Order By: Relevance
“…INPA R-991 isolated from soils of the Central Amazonian floodplain. The rhizobial strains were identified by partial sequencing of the 16S rRNA gene (Oliveira et al, 2007). Stock cultures were maintained on extract-mannitol agar (YMA) slants (Vincent, 1970) at 4 o C. The medium used for enzyme production was composed of (g L -1 ): 10.0 maltose, 0.4 K 2 HPO 4 , 0.1 K 2 HPO 4 , 0.2 MgSO 4 .7 H 2 O, 0.1 NaCl and 0.4 yeast extract.…”
Section: Indigenous Rhizobia Strains Culture Conditions and Inoculummentioning
confidence: 99%
See 1 more Smart Citation
“…INPA R-991 isolated from soils of the Central Amazonian floodplain. The rhizobial strains were identified by partial sequencing of the 16S rRNA gene (Oliveira et al, 2007). Stock cultures were maintained on extract-mannitol agar (YMA) slants (Vincent, 1970) at 4 o C. The medium used for enzyme production was composed of (g L -1 ): 10.0 maltose, 0.4 K 2 HPO 4 , 0.1 K 2 HPO 4 , 0.2 MgSO 4 .7 H 2 O, 0.1 NaCl and 0.4 yeast extract.…”
Section: Indigenous Rhizobia Strains Culture Conditions and Inoculummentioning
confidence: 99%
“…Nonetheless, studies on rhizobia amylases are still scarce. Recently, Oliveira et al (2006) reported the occurrence of extracellular amylases in rhizobia strains in solid and liquid media (Oliveira et al, 2007). The aim of this study was the production and characterization of extracellular amylases from two indigenous Central Amazonian rhizobia strains.…”
Section: Introductionmentioning
confidence: 99%
“…They have opened new frontiers of many commercial biotechnological processes including renewable energy, pharmaceuticals, saccharification or liquefication of starch, detergent industries, warp sizing of textiles, fibres, paper industries, foodstuffs, baking, clarification of haze formed in beer or fruit juices and for pretreatment of animal feed to improve digestibility [1]- [6]. Amylases are known to be produced by a variety of bacteria and fungi and their applications at industrial level have stimulated interest to explore their amylolytic activity in several microbes to be used as bioresources [2], [7]- [9]. The horizon got further magnified with the discovery of new strains of microorganisms and development of more efficient production strategies because microbes have substantial potential to contribute to several commercial purposes.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic characterization of Brazilian rhizobial strains has shown a great versatility of their potential to other biotechnological applications than inoculant production, such as production of microbial biopolymers (2,8,9), and enzymes with industrial application (19,20,21).…”
Section: Introductionmentioning
confidence: 99%